Tissue engineering of urinary organs - Park, KD; KWON, IL GREN; Kim, Young Ha (연세대학교의과대학, 2000)
Tissue engineering can serve as an alternative treatment for a malfunctioning or lost organ. isolated and expanded cells adhere to a temporary scaffold, proliferate, and secrete their own extracellular matrices (ECM) replacing the biodegrading scaffold. The genitourinary system, composed of the kidney, ureter, bladder, urethra, and genital organs, is exposed to a variety of possible injury sires from the time of Fetal development. All the urinary organs are mainly composed of smooch muscle and uroepithelial cells and which may be approached by tissue engineering techniques. A large number of materials, including naturally-derived and synthetic polymers have been utilized to fabricate prostheses for the genitourinary system. Usually, whenever there is a lack of native urologic tissue, reconstruction is considered with native non-urologic tissue, such as, gastrointestinal segments, or skin or mucosa from multiple body sites. Engineering tissues using selective cell transplantation may provide a means to create functional new genitourinary tissues. This review concerns urinary tissues reconstructed with bladder uroepithelial cells and smooth muscle cells (SMCs) implanted on biodegradable polymer matrices.